PENGARUH PERMODALAN, PENDAPATAN BUNGA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA BANK BUMN KONVENSIONAL DI INDONESIA - Widowati, Anya Devina; Abdullah, Mohammad Faisal; Arifin, Zainal (Journal of Financial Economics & Investment, 2022)
The purpose of this thesis research is to determine the effect of capital, interest income, and liquidity on the profitability of conventional state-owned banks in Indonesia. The data source from this study was obtained from the official website of the Financial Services Authority. The population from this study were 4 banks. The sample from this study used the census method. This study used panel data regression analysis. The results show that the partial test results of the Capital Adequacy Ratio variable has a positive and significant effect on Return on Assets, Net Interest Margin has a positive and significant effect on Return on Assets, and Loan to Deposit Ratio has a positive and significant effect on Return on Assets. Simultaneously, there is an effect of the variable Capital Adequacy Ratio, Net Interest Margin and Loan to Deposit Ratio on Return on Assets.